Teaching Exploratory Tests through PBL and JiTT: an experience report in a context of distributed teams - Coutinho, Jarbele; Andrade, Wilkerson; Machado, Patricia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
There is no specific professional responsible for quality assurance in agile teams, such as the Test Engineer. Thus, the skills, competencies, and attributions inherent to this professional are the responsibility of all team members. Due to Exploratory Testing (ET) benefits in agile development, there is a need to train agile professionals. In this sense, this paper aims to investigate the contributions and limitations of adopting Problem-Based Learning (PBL) and Just-in-Time Teaching (JiTT) in ET teaching-learning. For this, we conducted a course in remote learning format with agile developers, distributed geographically. Data were collected through an online questionnaire and examined with quantitative and qualitative analysis at the end of the course. Our main findings are that (1) the collaboration between the participants and the adoption of a real problem, along with (2) activities and resources made available before the class, and (3) the existence of specific tool support for ET sessions optimized learning in the context of remote learning.